2024
DOI: 10.3389/fphar.2024.1363131
|View full text |Cite
|
Sign up to set email alerts
|

Xie Zhuo Tiao Zhi formula ameliorates chronic alcohol-induced liver injury in mice

Kaixin Chang,
Rui Guo,
Wenbo Hu
et al.

Abstract: This study aimed to evaluate the protective role and potential mechanisms of Xie Zhuo Tiao Zhi decoction (XZTZ) on alcohol-associated liver disease (ALD). XZTZ significantly alleviated alcohol-induced liver dysfunction, based on histological examinations and biochemical parameters after 4-week administration. Mechanically, alcohol-stimulated hepatic oxidative stress was ameliorated by XZTZ, accompanied by the improvement of Nrf2/Keap1 expression and alcohol-activated phosphorylation of pro-inflammatory transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…93 Other studies have shown that Xie-Zhuo-Tiao-Zhi formula can alleviate alcohol-induced liver injury, oxidative stress, and inflammation possibly through modulation of Nrf2/Keap1 and MAPKs/NF-κB signaling pathways. 94 In the treatment of ALD, whether it is staged or based on type or evidence, traditional Chinese medicine thus has better effects. Traditional Chinese medicine can not only relieve patients’ pain, but also improve their quality of life, and its use to treat ALD in the future would be a very promising direction.…”
Section: Future Solutionsmentioning
confidence: 99%
“…93 Other studies have shown that Xie-Zhuo-Tiao-Zhi formula can alleviate alcohol-induced liver injury, oxidative stress, and inflammation possibly through modulation of Nrf2/Keap1 and MAPKs/NF-κB signaling pathways. 94 In the treatment of ALD, whether it is staged or based on type or evidence, traditional Chinese medicine thus has better effects. Traditional Chinese medicine can not only relieve patients’ pain, but also improve their quality of life, and its use to treat ALD in the future would be a very promising direction.…”
Section: Future Solutionsmentioning
confidence: 99%